Autocontrole de conhecimento de resultados na aquisição de habilidades motoras em idosos de diferentes faixas etárias - Cristiane Alves Martins (2020)
Effects of self-controlled knowledge of results (KR) have been demonstrated in studies with young adult learners. The use of effective strategies of KR request and increased intrinsic motivation are associated with the effects of self-control on the motor skills acquisition. Studies investigating self-controlled KR in elderly learners have not confirmed its effects on the acquisition of motor skills. The objective of this study was to investigate the effects of self-controlled KR on the motor skills acquisition, as well as the strategies of feedback request adopted by elderly people of different age groups. One experiments were carried out with elderly people of different age groups, youngest (M = 67.17 ± 1.6 years old), intermediate (M = 71.83 ± 1.55 years old), and oldest (M = 76.17 ± 1.34 years old). It was used a manual positioning task with pre-determined sequence and target time in acquisition, retention, and transfer phases. In each age condition, participants were divided in two groups, according to the condition of KR: Self-controlled (participants were provided with KR whenever they felt necessary) and yoked (feedback was controlled by the experimenter and its scheduling was paired to a participant of the self-controlled condition). In the youngest elderly, the self-controlled condition was superior to the yoked condition in the retention test. In the intermediate as well as the oldest condition, the self-controlled was similar to yoked groups in tests. Altogether, the results showed effects of self-controlled KR on the learning of youngest elderly people, as well as benefits of using strategies based on good performance. The use of strategies based both on good and poor performance, and on trials wherein the learner does not know the result was observed in elderly people of intermediate and more advanced ages, and these strategies did not seem to enhance learning. The information processing capacity is reduced with advancing age, and it seems to affect the leaning of the elderly.